Hepatoprotective Potential of Elsholtzia densa Against Acute and Chronic Models of Liver Damage in Wistar Rats - Zargar, Ovais Ahmad; Bashir, Rohina; Ganie, Showkat Ahmad; Masood, Akbar; Zargar, Mohammad Afzal; Hamid, Rabia (Drug Research, 2018)
The aim of the present study was to evaluate the hepatoprotective activity of methanolic extract of Elsholtzia densa against experimentally induced acute (CCl4) and chronic (paracetamol) liver injury in albino wistar rats. Activity was measured by monitoring the serum levels of ALT, ALP AST and LDH, total protein levels, bilirubin and albumin. The results of the CCl4 and paracetamol-induced liver toxicity experiments showed that the rats treated with the methanolic extract of Elsholtzia densa exhibited a significant decrease in biochemical parameters as well as the proteins, which were all elevated in the CCl4 and paracetamol group. The extract at a concentration of 300 mg/kg body wt. showed a significant decline (P≤0.05) in the levels of AST, ALT, ALP and LDH to 69.50±2.23IU/L, 60.01±2.25IU/L,46.20±2.24 IU/L and 150.21±5.68IU/L in CCl4 injected animals and 51.12±2.20 IU/L,49.15±3.25 IU/L, 44.12±2.56 IU/L and 125.15±4.45 IU/L in paracetamol-treated animals when compared to the control group. The activities of tissue antioxidants GSH, GPx, GR, GST and CAT was significantly (P≤0.05) restored in dose dependent manner in animals treated with extracts as with acute and chronic hepatotoxic models. The current study confirmed the hepatoprotective effect of methanolic extract of Elsholtzia densa against the model hepatotoxicant CCl4 and paracetamol.
Keywords: CCl4; Paracetamol; Antioxidants; Silymarin; Bilirubin